Fetishism and Form: Advertising and Ironic Distance in Don DeLillo’s White Noise - Adam Szetela (European Journal of American Studies)
This essay uses the historical framework of late twentieth-century advertising to understand issues of characterization in Don DeLillo’s novel White Noise. Given DeLillo’s prior career as a copywriter for Ogilvy & Mather, as well as a large body of scholarship that analyzes his novels in relationship to issues of political economy and American culture, this essay seeks to not only deepen an understanding of the historical issues that surround DeLillo’s work, but also the political implications of his writing. What is at stake in this project is the treatment of White Noise not only as a realistic “view of life in contemporary America” on par with Jean Baudrillard’s America (Wilcox 3246), but as a rebuke of the commodity fetishism central to the capitalist mode of production.